Four Element Microstrip Antenna Array with Electromagnetic Band Gap Structure and Silver Material Deposition for Reduced Mutual Coupling - Rao, K. Prahlada; R M, Vani; P V, Hunagund (Journal of Science and Technology, 2019)
This paper presents the performance of four element microstrip antenna array. The overall bandwidth of the microstrip antenna array with silver material coating is equal to 228.53 % as compared to 75.91 % without silver material coating. The microstrip antenna array with silver material coating of 30 mm thickness is producing good reduction in mutual coupling values at the resonant frequency of 5.53 GHz. Moreover, the radiation properties of antenna array are improved with good reduction in power radiated in the undesired direction. FR-4 glass epoxy substrate is used as dielectric substrate which has a dielectric constant of 4.2 and loss tangent of 0.0245. The microstrip antenna arrays are designed using Mentor Graphics IE3D software and the measured results are obtained using vector network analyzer.